Medication and nutrient administration considerations after bariatric surgery - Miller, April D.; Smith, Kelly M. (American journal of health-system pharmacy, 2006)
Medication and nutrient administration considerations after bariatric surgery are discussed. Bariatric surgery is categorized by surgical technique (i.e., restrictive procedure or a combination of restrictive and malabsorptive procedures). Roux-en-Y gastric bypass is the most frequently performed bariatric surgery in the United States. Patients who have undergone this surgery are at risk for nutrient deficiencies. Several factors, such as pH and absorption sites, should be considered when providing these patients with appropriate supplementation. Drug solubility and surface area for absorption are also affected by gastric bypass procedures. By bypassing major portions of the small intestine, Roux-en-Y procedures drastically reduce the surface area for absorption. These changes may warrant manipulation in drug route or dose to ensure adequate delivery. Drugs with long absorptive phases that remain in the intestine for extended periods are likely to exhibit decreased bioavailability in these patients. The reduced size of the stomach after surgery can place patients at risk for adverse events associated with some medications. Medications implicated in such adverse events include nonsteroidal antiinflammatory drugs, salicylates, and oral bisphosphonates. Drugs that are rapidly and primarily absorbed in the stomach or duodenum are likely to exhibit decreased absorption in patients who have had combination restrictive-malabsorptive procedures. Because reduced drug absorption may result in decreased efficacy rather than toxicity, increased patient monitoring for therapeutic effects can help detect potential absorption problems. Selection of appropriate nutrient salts can improve nutrient replacement in patients who have undergone bariatric surgery. Changes in dosage forms based on drug characteristics can improve bioavailability.